2021
DOI: 10.17159/wsa/2021.v47.i2.10913
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the frequency of drought/flood severity in the Luvuvhu River catchment, Limpopo Province, South Africa

Abstract: The Luvuvhu River catchment experiences rainfall variability with a high frequency of extremely dry and wet conditions. Understanding the frequency of drought and floods in this catchment area is important to the agriculture sector for managing the negative impacts of these natural hazards. This study was undertaken to investigate the frequency and severity of drought/floods and linkages with the El Niño Southern Oscillation (ENSO) phenomenon. Poor and resource-limited small-scale farmers in the Luvuvhu River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Linkages between the frequency and intensity of droughts and flooding have been seen in the El Nino Southern Oscillation (ENSO) phenomenon [ 21 ]. The flood disaster that occurred in December 2010–January 2011 was linked to a La Nina event and caused massive displacement of people and numerous deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Linkages between the frequency and intensity of droughts and flooding have been seen in the El Nino Southern Oscillation (ENSO) phenomenon [ 21 ]. The flood disaster that occurred in December 2010–January 2011 was linked to a La Nina event and caused massive displacement of people and numerous deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Since rainfall is a major contributor to reservoir water resources, a reduction in annual precipitation negatively impacts water supply to different water users. Studies focused on drought such as [18][19][20][21][22] have been conducted in the LRC. However, these aimed to characterise, assess, and predict drought events and not much attention has been directed to evaluate the relationship between El Niño-induced drought and reservoir water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Ekwezuo et al [5] analyzed the regional characteristics of meteorological drought and flood in West Africa and found that the severity of drought in the region showed a decreasing trend, while the severity of floods increased; however, droughts and floods have always been the biggest threats to food production and security in West Africa. Scholars have evaluated the frequency of drought/flood severity in the Luvuvhu River basin, Limpopo Province, South Africa, and found that the frequency of moderate to severe drought increased from south to north, with most of the basin affected by severe drought, sloping to the northeast of the basin, and the northwestern parts of the basin experienced a high frequency of severely wet to extremely wet conditions [6]. Research has shown that meteorological drought in the Yellow River basin (YRB) has been increasing, and its distribution is expanding [7][8][9], while drought has shown a decreasing trend on both seasonal and annual scales [10].…”
Section: Introductionmentioning
confidence: 99%